A web-based travel package management system integrated with QR code / Naemah Abdul Wahab and Norhaslinda Jamil - Abdul Wahab, Naemah; Jamil, Norhaslinda (UiTM Cawangan Perlis, 2024)
The tourism industry is associated with people travelling either domestically or abroad, for business, social, or recreational reasons. This industry integrates numerous services and activities such as tourism organization, marketing, hotel industry, transportation services, food and beverage activities, retail stores and various other activities under one umbrella. In addition to generating income and jobs, tourism is the best way to promote the nation's image. As the economy and living conditions have improved, so too has the tourist sector, and more people are turning to vacations as a way to alleviate stress and unwind. Currently, travel agencies handle a lot of data with low efficiency and a lot of mistakes. Therefore, this study developed a comprehensive integration of QR code for package travel management system that caters to users in Malaysia, offering functionalities such as itinerary customization, QR code generation and access to essential travel information. The development of this project adopts the Waterfall Methodology, encompassing phases such as planning, requirement analysis, design, implementation and testing. The application is crafted using the Visual Studio Code. The study conducted a User Acceptance Testing (UAT) using questionnaires to evaluate the system's effectiveness and user-friendliness to thirty respondents including family members of frequent travellers and randomly selected community members. Positive feedbacks with Perceived Ease of Use (PEU) scoring 3.6, Attitude of Using (ATT) at 3.7, Perceived Usefulness (PU) scoring 3.4, and Intention to Use (IU) obtaining 3.9, were gathered from the analysis and findings that emphasizing the QR code system's potential as a cost-effective and efficient solution for travellers to monitor and optimize their travel experiences. Future work involves adding maps for easy navigation and implementing augmented reality (AR) for virtual destination previews.